Diagnosis of Nipple Discharge: Value of Magnetic Resonance Imaging and Ultrasonography in Comparison with Ductoscopy - Yılmaz, Ravza (Balkan Med J, 2017)
BACKGROUND: Pathologic nipple discharge, which is a common reason for referral to the breast imaging service, refers to spontaneous or bloody nipple discharge that arises from a single duct. The most common cause of nipple discharge is benign breast lesions, such as solitary intraductal papilloma and papillomatosis. Nevertheless, in rare cases, a malignant cause of nipple discharge can be found. AIMS: To study the diagnostic value of ultrasonography, magnetic resonance imaging, and ductoscopy in patients with pathologic nipple discharge, compare their efficacy, and investigate the importance of magnetic resonance imaging in the diagnosis of intraductal pathologies. STUDY DESIGN: Diagnostic accuracy study. METHODS: Fifty patients with pathologic nipple discharge were evaluated by ultrasonography and magnetic resonance imaging. Of these, 44 ductoscopic investigations were made. The patients were classified according to magnetic resonance imaging, ultrasonography, and ductoscopy findings. A total of 25 patients, whose findings were reported as intraductal masses, underwent surgery oincluding endoscopic excision for two endoscopic excision. Findings were compared with the pathology results that were accepted as the gold standard in the description of the aetiology of nipple discharge. In addition, magnetic resonance imaging, ultrasonography and ductoscopy findings were analysed comparatively in patients who had no surgery. RESULTS: Intraductal masses were reported in 26 patients, 20 of whom operated and established accurate diagnosis of 18 patients on magnetic resonance imaging. According to the ultrasonography, intraductal masses were identified in 22 patients, 17 of whom underwent surgery. Ultrasonography established accurate diagnoses in 15 patients. Intraductal mass was identified in 22 patients and ductoscopy established accurate diagnoses based on histopathologic results in 16 patients. The sensitivities of methods were 75% in ultrasonography, 90% in magnetic resonance imaging, and 94.6% in ductoscopy. The specificities were 66.7% in ultrasonography, 66.7% in magnetic resonance imaging, and 40% in ductoscopy. Intraductal papillomas were mostly observed as oval nodules with well-circumscribed smooth margins within dilated ducts and persistant in the dynamic analysis. Lesions that protruded into the lumen of the ducts, either solitary or multiple, were characteristic ductoscopy findings of our patients who were diagnosed as having papilloma/papillomatosis. CONCLUSION: Magnetic resonance imaging and ductoscopy had no statistical superiority over each other, however they were superior to ultrasonography in the diagnosis of pathologic nipple discharge. Magnetic resonance imaging may be highly sensitive for diagnosing nipple discharge with new techniques and sequences and a non-invasive method that more advantageous for showing ductal tree visualization and is able to detect completely obstructed intraductal lesions.